Systematic discovery of rab GTPases with synaptic functions in Drosophila. - Chan, C.C.; Scoggin, S.; Wang, D.; Cherry, S.; Dembo, T.; Greenberg, B.; Jin, E.J.; Kuey, C.; Lopez, A.; Mehta, S.Q.; Perkins, T.J.; Brankatschk, M.; et al. (Current Biology, 2011)
Neurons require highly specialized intracellular membrane trafficking, especially at synapses. Rab GTPases are considered master regulators of membrane trafficking in all cells, and only very few Rabs have known neuron-specific functions. Here, we present the first systematic characterization of neuronal expression, subcellular localization, and function of Rab GTPases in an organism with a brain.We report the surprising discovery that half of all Drosophila Rabs function specifically or predominantly in distinct subsets of neurons in the brain. Furthermore, functional profiling of the GTP/GDP-bound states reveals that these neuronal Rabs are almost exclusively active at synapses and the majority of these synaptic Rabs specifically mark synaptic recycling endosomal compartments. Our profiling strategy is based on Gal4 knockins in large genomic fragments that are additionally designed to generate mutants by ends-out homologous recombination. We generated 36 large genomic targeting vectors and transgenic rab-Gal4 fly strains for 25 rab genes. Proof-of-principle knockout of the synaptic rab27 reveals a sleep phenotype that matches its cell-specific expression.Our findings suggest that up to half of all Drosophila Rabs exert specialized synaptic functions. The tools presented here allow systematic functional studies of these Rabs and provide a method that is applicable to any large gene family in Drosophila.